Epidemiological Status of Dermatophytosis in Guilan, North of Iran - Ali Akbar Fallahi (Current Medical Mycology, 2017)
Background and Purpose: The epidemiological features of dermatophytoses have been characterized in many geographical locations of Iran, but not in Guilan, North of Iran. This study was carried out to determine the distribution pattern of dermatophytoses and their relevant agents in Guilan, North of Iran, over a period of one year, from April 2010 to April 2011. Materials and Methods: The clinical samples of skin, hair, and nail from 889 outpatients (317 men vs. 572 women) were used for direct microscopy and culture. All the culture-positive samples were then subjected to amplification of the internal transcribed spacer (ITS) of the nuclear rDNA followed by a restriction fragment length polymorphism (RFLP) assay to verify the causative agents. Results: The infection was confirmed in 90 (44.3%) males and 113 (55.7%) females.The most common type of dermatophytoses was tinea cruris (42.9%), followed by tinea pedis (20.2%), tinea corporis (11.3%), tinea unguium (7.4%), tinea faciei (6.9%), tinea manuum (6.4%), and tinea capitis (4.9%). ITS-RFLP based of the identification of isolates, showed that the infections were significantly associated with anthropophilic species, of Trichophyton rubrum (41.9%), Epidermophyton floccosum (19.7%), T.tonsurans (5.4%), and T. violaceum (2%). Other causative agents were T. interdigitale (22.6%),Microsporum canis (4.9%), T. verrucosum (2.5%), and M. gypseum. (1%). Conclusion: The higher prevalence of T. rubrum, as the agent of dermatophytoses, than other species has never been reported from Iran and is of public health concern because of the chronic nature of infections with anthropophilic species. To thoroughly investigate the epidemiological trend of dermatophytoses in Iran, further periodical and molecularbased studies are necessary.